Proyecto de sistema de control de flujo de tránsito aéreo para aeropuertos - Rivera Herbozo, Alfredo Henrry (2022)
The constant delay in confirming the aircraft landing time, the lack of supply of control tower personnel for coordination purposes, as well as the insufficient adequate documentation that generates greater ease of access to air procedures, these are the continuous difficulties that the International Airport is going through. Taking into account this current problem, the general objective of this project is to inform about the air traffic of the Airport and as specific objectives to facilitate and document the work of the Flow Control area of the Airport when managing the hours landing and take-off of flights arriving from different airports in Peru. For this, the development of a web system is proposed that improves the work process carried out by the operators through the use of Cloud Computing Technology using a public cloud under the PaaS (Platform as a Service) model, because the application is on servers that facilitate the management and development of system sources and their data. For the development of this project, the Scrum framework was used, which allows managing both development and testing. Among the improvements obtained for the client, the development of three prototypes was presented that were adjusted to the reality, need and vision of the user. Although the project had a high degree of automation in the main process of the landing time request queuing, it was modified at the request of the user, which requires greater control over the editing of the requests.